Comparison of different linearized plasma response models on the EAST tokamak. (9th May 2018) - Chen, S.L.; Villone, F.; Sun, Y.W.; Xiao, B.J.
Abstract: In this paper, experimental growth rates are positively compared to numerical predictions for the new geometry of the experimental advanced superconducting tokamak (EAST) and for a wide variety of plasma equilibrium configurations; hence, significantly extending the validation range as compared to previous works. The general results confirmthat the CarMa0 code is adequate to reproduce the experimental situation in EAST. In addition, we investigate the effects of different assumptions on the plasma response model, on the structures and on plasma boundary.